Thermal conductivity of bottom sediments in the East Siberian Arctic seas: a case study in the Buor-Khaya Bay; 68th Canadian Geotechnical Conference and 7th Canadian Permafrost Conference: GEOQuebec 2015, Quebec, September 20-23, 2015 - Chuvilin E. M. Evgeny Mikhaylovich; Bukhanov B. A. Boris Aleksandrovich; Grebenkin S. I. Sergey Igorevich; Tumskoy V. E. Vladimir Evgenjevich; Shakhova N. E. Nataljya Evgenjevna; Dudarev O. V. Oleg Viktorovich; Semiletov I. P. Igor Petrovich (2015, 2015)
Title screen